Effect of CO2 Addition on Preparation of Diamond Films by Direct-Current Hot-Cathode Plasma Chemical Vapor Deposition Method - 张春梅 郑艳彬 姜志刚 吕宪义 侯雪 胡双 刘军伟 (Chinese physics letters, 2010)
Diamond films are deposited on Mo substrates by dc hot-cathode plasma chemical vapor deposition method using a CH4-H2-CO2 gas mixture. Adjusting the flow of CO2, we study the relevant influence on surface morphology, grain orientation and crystalline quality of films with scanning electron microscopy, x-ray diffraction, Raman spectroscopy, respectively. The results show that grain orientation of the films has a transition with the increasing CO2 addition, from （100） orientation to （110） orientation and then （111） orientation. The crystalline quality is improved but the growth rate is decreased by raising the flow of CO2. The experimental results are also discussed briefly.